Sara Lipska — artystka wszechstronna. Wyjątkowa uczennica Dunikowskiego - Ziembińska, Ewa (Archiwum Emigracji. Studia – Szkice – Dokumenty, 2012)
Sara Lipska (1882–1973) was talented in several fine arts. She worked with sculpture and painting; designed interiors as well as theatre sets and costumes; she even worked as a book illustrator. She spent most of her professional life in Paris, where she associated herself with the artistic avant-garde and where she enjoyed great success. Her relationship with Dunikowski influenced her life immensely. They met at the School of Fine Arts in Warsaw, where he taught sculpture as a young professor and where she began to study in 1904. In Paris she worked for Sergey Diaghilevs’ Ballets Russes performing at the Paris Grand Opera and for Antoine Cierplikowski, a well-known hairdresser and a fashion designer of Polish origins. Sara Lipska’s artistic output shows that she moved among the best Parisian circles. The artist exhibited her works, among others, at several Paris Salons.